Mengevaluasi Efisiensi Pengontrol Input-Output dalam Arsitektur Komputer Modern - Selpi Amanda Fadilah; Muhamad Rizky; Sukira Sukira; Didik Aribowo (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2023)
Input and output devices are a system that exists on a computer. A computer is a system consisting of various specific components. These components will later be connected to each other and work together, to carry out processes so that they can produce information. In general, the function of a computer is to receive, process and produce data output, various forms of information in the form of text, audio, images or video. The method used in this research is an adapted literature study, and the research flow is described as follows. Figure 1 shows the data collection method used in this research. The purpose of this data collection is to obtain data that will be analyzed and processed so that any existing problems can be found and it is hoped that this research will find solutions to these problems. To collect data, study the literature. This research uses hardware and software to prove the input devices and output devices that are usually used in organizing computers. The characteristics of the I/O system are influenced by the technology of other components, for example the processor. The performance of the I/O system is more complex than the processor. Therefore, increasing CPU time without directly increasing I/O time does not necessarily improve system I/O performance. Computer system performance can be improved by improving hardware and software component technology. In this research, the focus is on I/O device performance, specifically I/O time. This research examines the relationship between CPU time, I/O time, and elapsed time. The results show that increasing CPU time results in increasing I/O time. I/O system performance is very important for computer users. Response time, also known as total elapsed time, is an important performance measure, especially for single-user and personal computers. In commercial computing, high throughput and short response times are required. Behavior, partners, and data rate are three characteristics used to evaluate I/O systems. The performance of a computer system is determined by various factors, including different users, performance measures, and aspects of the system. Performance improvements can be achieved by improving hardware factors that support overall system performance. Performance measurement can be done through response time (execution time) or throughput. Response time aims to minimize the time between starting and completing a task, while higher throughput can be achieved by serving multiple requests simultaneously. Based on research, it can be concluded that the quality of input, process and output in Islamic educational institutions is influenced by various factors. Student input is critical in determining the quality of education, and the institution has implemented a selective process to ensure the admission of motivated and dedicated students. The educational process is characterized by the application of discipline, adherence to schedules, and the instillation of religious values. The institution's output is reflected in the academic achievements of its students, as well as their motivation and participation in various competitions and activities. This research uses a qualitative approach with a case study method, collecting data through documentation and observation. Data analysis was carried out using triangulation and interpreted qualitatively. This study highlights the importance of a holistic approach to education, integrating religious values, community support, and parental involvement to improve the quality of education.